Cellular Peptidases in Immune Functions and Diseases 2 - Langner, Jürgen; Ansorge, Siegfried (Advances in Experimental Medicine and Biology, 2000)
Of the many special roles played by proteolytic enzymes in immune reactions, this study addresses different aspects of membrane peptidases, signal transduction via ligation of membrane peptidases (especially of dipeptidyl peptidase IV/CD26 and aminopeptidase N/CD13), and regulation of membrane peptidases in vivo and in vitro. A number of newly discovered peptidases (including cathepsin F, W and X, carboxypeptidase X, attractin) are described, with special emphasis given to the role of peptidases in immune and defense reactions and in the pathogenesis of inflammatory and other diseases, including rheumatoid arthritis, pancreatitis, multiple sclerosis, Alzheimer's disease and tumours of various origins. The focus on the involvement of a selection of proteolytic enzymes in immune reactions and diseases is a useful feature of this multifaceted work , which combines biochemical, immunological and clinical research reports with literary reviews of the field.